Modeling the PV generator behavior submit to the open-circuit and the short-circuit faults, ISSN/ISBN 1974-9821/1974-983X - Rezgui Wail Mouss Kinza Nadia Mouss Leila Hayet (IREMOS International Review on Modelling and Simulations., 2014)
In this paper, we proposed a new mathematical model of a faulty photovoltaic generator operation. It presents its behavior, when it's subjected to the open-circuit and the short-circuit faults at its basic components as: cells, bypass diodes and blocking diodes. Such kind of modeling will allow developing fault detection and diagnosis methods. Indeed, the proposed model will be used to set normal and fault operation conditions database, which will facilitate learning and classifications phases.